Aristolochia emiliae (Aristolochiaceae: Subsección Pentandrae), una especie nueva de la costa de Jalisco, México - Santana-Michel, Francisco J.; Solís-Magallanes, José Arturo (Instituto de Ecología, A.C., 2008)
Aristolochia emiliae sp. nov., found in tropical deciduous forest in the Estación de Investigación, Experimentación y Difusión “Chamela”, municipality of La Huerta, Jalisco, Mexico, is described and illustrated. The geniculate flowers are less than 3 cm long with uncinate hairs on the orbicular calyx limb. The basal lobes of the trilobate leaves are anchor-shaped, a unique characteristic among the Mexican species in the Pentandrae subsection of Aristolochia.